FOREIGN TRADE OF KOSOVO AND IMPACT OF FISCAL POLICY - Berisha, Agim (European Scientific Journal, ESJ, 2012)
Negative trading balance is only one of the economical problems by which Kosovo is facing. Kosovo institutions are aware that change of this reality requires a comprehensive economical and political approach and reforms in a manner to change operational environment, with a view to improve competitive position of Kosovo in global market. Kosovo is public-spirited for trade liberalization. The participation in regional and worldwide mechanisms for facilitation of trade was one of the main objectives of the policies of the Kosovo’s institutions. Expansion of the trade in Kosovo through market liberalization must take into consideration three aspects: a) Rationalization and substitution of import, b) Facilitation of trade and c) Export promotion. Trade is a multidimensional concept which has influence almost in all social and economical fields of life. However, the international trade of Kosovo is dominated by imports, whereas the export is in the lowest level, resulting in this way in a high commercial deficit .So, the Kosovo since the after conflict period is very dependant by the import and trends indicate that in a short time period is very difficult to be expected considerable changes.